Nowy zmodyfikowany ogólny system preferencji celnych Unii Europejskiej - Rudnicka, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
In 1971 the European Community implemented a Generalized System of Preferences under which industrialized countries grant unilateral preferential treatment to developing countries. The present EU's GSP came into force on 1 January 2006. It targets preferences on those countries which need them most and shifts the focus on the concept of sustainable development. As compared to the previous scheme, the new regulation provides for three arrangements instead of five: the general arrangements, the special incentive arrangements to promote sustainable economy, and the special arrangements for least developed countries (LDCs). Under the general arrangements, duties on imports of non-sensitive products are exempted, while duties on imports of sensitive products are reduced. The special incentive arrangements provide additional tariff preferences available for countries complying with international standards concerning in particular human rights, workers' rights and protection of the environment. The UE's GSP grants duty-free access to imports of all products from LDCs, except arms and munitions. Even though, GSP has proved to be one of the most effective tools to help developing countries to enhance their export earnings, promote their industrialization, encourage the diversification of their economies and compete on international markets, it is necessary to stress that nowadays tariffs are not of great importance in foreign trade. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 300-308